Lower respiratory tract infection in sudden unexpected infant deaths - Van der Heyde, Yolande (Division of Anatomical Pathology, 2015)
Pneumonia due to polymicrobial infection is known to increase the severity and risk of fatality among young children. A retrospective study was undertaken on Sudden Unexpected Infant Death cases occurring, between 1 May and 30 September 2009, which were admitted to a medico-legal mortuary servicing the Cape Town western metropole. Published studies have shown the risk factors for lower respiratory tract infection to include lack of breast feeding, prenatal and environmental tobacco smoke exposure, prematurity, immunosuppression, underlying medical conditions and overcrowding. The present study was aimed at determining which of the known epidemiological factors were associated with SUDI death types admitted to this mortuary and to describe the associated histopathology. In addition, in the knowledge that drugs, specifically Methamphetamine are widely used on the Cape Flats from where almost all this mortuary's SUDI cases are derived, this study has attempted to find out whether or not the usage of drugs by the caregiver at the time of infant death was another independent risk factor in SUDI deaths.